Practice questions available in McGraw Hill Math Grade 6 Answer Key PDF Lesson 6.3 Adding Fractions with Like Denominators will engage students and is a great way of informal assessment.
McGraw-Hill Math Grade 6 Answer Key Lesson 6.3 Adding Fractions with Like Denominators
Exercises
Add Fractions
Question 1.
\(\frac{1}{2}\) + \(\frac{3}{2}\)
Answer:
\(\frac{1}{2}\) + \(\frac{3}{2}\) = 2.
Explanation:
Question 2.
\(\frac{7}{3}\) + \(\frac{6}{3}\)
Answer:
\(\frac{7}{3}\) + \(\frac{6}{3}\) = 4 \(\frac{1}{3}[/latex
Explanation:
Question 3.
[latex]\frac{6}{11}\) + \(\frac{6}{11}\)
Answer:
\(\frac{6}{11}\) + \(\frac{6}{11}\) = 1\(\frac{1}{11}\)
Explanation:
Question 4.
\(\frac{5}{19}\) + \(\frac{2}{19}\)
Answer:
\(\frac{5}{19}\) + \(\frac{2}{19}\) = \(\frac{7}{19}\)
Explanation:
Question 5.
\(\frac{3}{7}\) + \(\frac{6}{7}\)
Answer:
\(\frac{3}{7}\) + \(\frac{6}{7}\) = 1 \(\frac{2}{7}\)
Explanation:
Question 6.
\(\frac{4}{3}\) + \(\frac{2}{3}\)
Answer:
\(\frac{4}{3}\) + \(\frac{2}{3}\) = 2.
Explanation:
Question 7.
\(\frac{1}{5}\) + \(\frac{4}{5}\)
Answer:
\(\frac{1}{5}\) + \(\frac{4}{5}\) = 1.
Explanation:
Question 8.
\(\frac{9}{33}\) + \(\frac{17}{33}\)
Answer:
\(\frac{9}{33}\) + \(\frac{17}{33}\) = \(\frac{26}{33}\)
Explanation:
Question 9.
Answer:
\(\frac{1}{10}\) + \(\frac{7}{10}\) = \(\frac{4}{5}\)
Explanation:
Question 10.
Answer:
\(\frac{22}{37}\) + \(\frac{14}{37}\) = \(\frac{36}{37}\)
Explanation:
Question 11.
Answer:
\(\frac{16}{97}\) + \(\frac{32}{97}\) = \(\frac{48}{97}\)
Explanation:
Question 12.
Answer:
\(\frac{14}{23}\) + \(\frac{3}{23}\) = \(\frac{17}{23}\)
Explanation:
Question 13.
Answer:
\(\frac{10}{13}\) + \(\frac{7}{13}\) = 1\(\frac{4}{13}\)
Explanation:
Question 14.
Answer:
\(\frac{5}{9}\) + \(\frac{2}{9}\) = \(\frac{7}{9}\)
Explanation:
Question 15.
Answer:
\(\frac{10}{39}\) + \(\frac{23}{39}\) = \(\frac{11}{13}\)
Explanation:
Question 16.
Answer:
\(\frac{1}{4}\) + \(\frac{3}{4}\) = 1.
Explanation:
Question 17.
Answer:
\(\frac{4}{14}\) + \(\frac{4}{14}\) = \(\frac{4}{7}\)
Explanation:
Question 18.
Answer:
\(\frac{5}{7}\) + \(\frac{8}{7}\) = 1\(\frac{6}{7}\)
Explanation: